The Effect of Weather Factors On the Population Dynamics of Reduviids (Insecta: Heteroptera: Reduviidae) From Semi-Arid Area of Sivakasi Taluk, Virudhunagar District, Tamil Nadu - Durkga, S. Jaya; Sudarmani, D.N.P.; Sundareswari, C. (International Journal of Scientific Research in Biological Sciences, 2019)
The species of the reduviid bugs of family Reduviidae under Order Heteroptera (Insecta: Reduviidae) is not only one of the most abundant groups but also showing significant economics and high scientific value. Many reduviid species play an important role in the food chain of animals and plants, as well as the ecological balance. Population dynamics of reduviid bugs were studied during June 2018- March 2019 in semi-arid area in Sivakasi Taluk. The reduviids were randomly collected and identified some field records. A total of 11 species belonging to 5 subfamilies were identified in selected study area. During the study period maximum numbers of reduviid bugs were recorded during the November 2018 and minimum numbers of reduviid bugs were recorded during March 2019. Monthly variation in relative abundance of reduviid population also noted. Various diversity indices were recorded and correlation co-efficient studies were carried out between reduviid bug diversity and weather parameters.